2015
DOI: 10.2166/ws.2015.081
|View full text |Cite
|
Sign up to set email alerts
|

The effect of length of free-surface gated circular conduit on air-demand ratio and aeration efficiency

Abstract: Aeration is the process of bringing water and air into close contact in order to increase dissolved oxygen concentration. The concentration of dissolved oxygen is an important indicator of water quality because aquatic life lives on the dissolved oxygen in the water. The hydraulic structures can be accepted as the key components in increasing dissolved oxygen concentration because of the strong turbulent mixing associated with substantial air bubble entrainment at these structures. Closed conduit is a classic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The impact of the Froude number on oxygen transport was examined by Aydin [26], which is an important metric in hydraulic engineering. The results from this study (as shown in figure 6) are consistent with prior research [27][28][29][30][31] in demonstrating that this dimensionless parameter has a significant influence on oxygen transfer.…”
Section: Discussionsupporting
confidence: 91%
“…The impact of the Froude number on oxygen transport was examined by Aydin [26], which is an important metric in hydraulic engineering. The results from this study (as shown in figure 6) are consistent with prior research [27][28][29][30][31] in demonstrating that this dimensionless parameter has a significant influence on oxygen transfer.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that injecting air into the flow downstream of the gate can significantly reduce the risk of cavitation damage. The air-demand ratio and the aeration efficiency in gated closed conduits have been investigated by Aydin et al (2021Aydin et al ( , 2022Aydin et al ( , 2023, Baylar and Batan (2010), Baylar et al ( , 2021Baylar et al ( , 2022, Campbell and Guyton (1953), Haindl and Sotornik (1957), Hohermuth (2017Hohermuth ( , 2019, Hohermuth et al (2020), Kalinske and Robertson (1943), Mortensen (2009), Mortensen et al (2011Mortensen et al ( , 2012, Mortensen and Kubitschek (2016), Oveson (2008), Ozkan et al (2006aOzkan et al ( , 2006bOzkan et al ( , 2010Ozkan et al ( , 2014Ozkan et al ( , 2015, Rajaratnam (1962), Safavi et al (2008), Sharma (1976), Speerli (1999), Speerli and Hager (2000), Tuna et al (2014), Unsal et al (2008Unsal et al ( , 2009Unsal et al ( , 2014, USACE (1964), Wisner (1965).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies on air‐demand ratio and the oxygen transfer efficiency in closed conduits were carried out by investigators (e.g. Campbell & Guyton, 1953; Escarameia, 2007; Haindl & Sotornik, 1957; Kalinske & Robertson, 1943; Mahmoudi‐Rad & Najafzadeh, 2021; Mortensen, 2009; Mortensen et al, 2011, 2012; Oveson, 2008; Ozkan et al, 2006, 2014, 2015; Rajaratnam, 1962; Shamsaei & Soleymanzadeh, 2006; Sharma, 1976; Speerli, 1999; Speerli & Hager, 2000; Speerli & Volkart, 1997; Stahl & Hager, 1999; Tuna et al, 2014; Unsal et al, 2008, 2009; USACE, 1964; Wisner, 1965). The comprehensive literature search did not identify any published analytical or physical studies investigating the role of cross‐sectional geometry of high‐head gated conduit in oxygen transfer efficiency.…”
Section: Introductionmentioning
confidence: 99%